First detection of porcine circovirus type 2e in Europe. (January 2022) - Franzo, G.; Ustulin, M.; Zanardelli, P.; Castellan, A.; Villa, N.; Manfredda, A.; Vio, D.; Drigo, M.
Highlights: First detection and genetic characterisation of the PCV-2e genotype in Europe. PCV-2e was detected in the absence of PCV disease-related clinical signs in Italian sows. Follow-up breeder herd study demonstrated persistent PCV-2e subclinical circulation. More intensive monitoring activities of asymptomatic animals is needed. Efficacy of current vaccines and diagnostic tools requires further evaluation. Abstract: Porcine circovirus 2 (PCV-2) infections are among the most economically important in swine farming. Because of the high evolutionary rate of PCV-2, several variants have emerged and are currently classified into several genotypes. However, only three (i.e. PCV-2a, PCV-2b, and PCV-2d) have a worldwide distribution, with other genotypes restricted to certain geographical regions and/or for limited time periods. Underdiagnosis or underreporting of these genotypes cannot be excluded. This is the first report of the detection and genetic characterisation of the PCV-2e genotype in Europe, from sows on a farm in Italy showing no clinical evidence of porcine circovirus disease. A follow-up study demonstrated persistent subclinical evidence of PCV-2e on the farm, at low frequency and viral load. This incidental finding emphasises the need for more intensive routine monitoring activities involving asymptomatic animals, coupled with DNA sequencing and data sharing. Considering the relevant genetic and phenotypic divergence of such genotypes, the actual efficacy of currently applied vaccines and diagnostic assays should be further evaluated.